TRAINING OF FUTURE TEACHERS TO THE WORK IN PRIMARY SCHOOL IN RURAL AREA - Onyshkiv, Zinoviy (Proceedings of National Aviation University (archive), 2014)
This article outlines the main directions of research on primary education in rural areas. The results of studies on the preparation of teachers to the educational process in primary schools in rural areas in national educational research were analyzed